PENGARUH ENVIRONMENTAL PERFORMANCE DAN ENVIRONMENTAL DISCLOSURE TERHADAP ECONOMIC PERFORMANCE - Bayu Aji Wijaya; Muhammad Nuryatno (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2014)
The objective of this study is to determine the impact of environmental performance and environmental disclosure to economic performance. This type of research conducted is the type of research by testing the hypothesis which is a study in explaining the phenomenon of the relationship between variabels. Data used in this study come from annual reports of basic & chemical industry companies listed on the Indonesia Stock Exchange and PROPER in 2011-2013 with a total of 13 companies. Analysis of the hypothesis used in this study using single linear regression and prior to hypothesis testing has been conducted test data normaliol. From the results obtained by testing the hypothesis that environmental performance affect the economic performance. Test results on the second hypothesis also suggests that environmental disclosure does not influence economic performance. The first .findings of the research support Suratno, et al (2006). While the latter findings support the findings of Ingram and Frazier (1980).